Indonesia's Carbon Trade Odyssey: An Analysis of Maqashid Sharia in Balancing Environmental and Economic Compromises - Idris, Bani; Hasan, Muhammad Toha; Sidik, Firdan Fadlan (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2023)
Abstract: This research is prompted by the emergence of carbon trading, involving the buying and selling carbon credits driven by climate change and greenhouse gas emissions impacting global stability. Indonesia's tropical forests, which can absorb 25.18 billion tons of carbon emissions, position the country for carbon trading transactions with developed nations. The study aims to assess Indonesia's efforts in reducing greenhouse gas emissions by harnessing the economic value of carbon. The research employs a descriptive qualitative approach with a normative juridical focus, and the research draws on primary sources such as laws, OJK regulations, DSN-MUI fatwas, ministerial regulations, and Islamic law about carbon trading and the green economy. Secondary data from literature, including books, journals, articles, and online news, complements the primary sources. Key findings include Indonesia's commitment to emissions reduction through forest and land-use empowerment, aligning with Maqashid Sharia principles. The economic value of carbon proves instrumental in implementing efficient, effective, and equitable mitigation and adaptation measures, fostering environmental sustainability, economic opportunities, improved welfare, reduced emissions, and green project promotion. By integrating Maqashid Sharia, carbon trading reflects low-carbon principles for preserving life and intellect, while resource efficiency aligns with offspring and wealth preservation. This Sharia-based green economy approach addresses inequality issues stemming from the uneven distribution of green production factors, guided by principles of justice, public interest, and equality.Abstrak: Penelitian ini dipicu oleh munculnya perdagangan karbon, melibatkan pembelian dan penjualan kredit karbon yang dipicu oleh perubahan iklim dan emisi gas rumah kaca yang mempengaruhi stabilitas global. Hutan tropis Indonesia, yang dapat menyerap 25,18 miliar ton emisi karbon, menempatkan negara ini untuk melakukan transaksi perdagangan karbon dengan negara-negara maju. Penelitian ini bertujuan untuk menilai upaya Indonesia dalam mengurangi emisi gas rumah kaca dengan memanfaatkan nilai ekonomi karbon. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan fokus yuridis normatif, dan mengandalkan sumber-sumber utama seperti undang-undang, peraturan OJK, fatwa DSN-MUI, peraturan menteri, dan hukum Islam tentang perdagangan karbon dan ekonomi hijau. Data sekunder dari literatur, termasuk buku, jurnal, artikel, dan berita online, melengkapi sumber-sumber utama. Temuan utama termasuk komitmen Indonesia dalam mengurangi emisi melalui pemberdayaan hutan dan penggunaan lahan, sejalan dengan prinsip Maqashid Sharia. Nilai ekonomi karbon membuktikan pentingnya dalam mengimplementasikan langkah-langkah mitigasi dan adaptasi yang efisien, efektif, dan adil, mendorong keberlanjutan lingkungan, peluang ekonomi, kesejahteraan yang meningkat, emisi yang berkurang, dan promosi proyek-proyek hijau. Dengan mengintegrasikan Maqashid Sharia, perdagangan karbon mencerminkan prinsip rendah karbon untuk melestarikan hidup dan akal, sementara efisiensi sumber daya sejalan dengan pelestarian keturunan dan kekayaan. Pendekatan ekonomi hijau berbasis Sharia ini mengatasi masalah ketidaksetaraan yang timbul dari distribusi faktor produksi hijau yang tidak merata, dipandu oleh prinsip keadilan, kepentingan umum, dan kesetaraan.